Optimization of Low-Calorific Coal Application at Different Loads in 600 MW Supercritical Thermal Power Plant with the PROMETHEE-GAIA Method - Ali Riza Motorcu; Hülya Demirören; Aykut Emir (Journal of Advanced Research in Natural and Applied Sciences)
This study examined the 600 MW supercritical unit of a 1200 MW imported coal-fired thermal power plant in Çanakkale, Türkiye. Coal blends consisting of low-calorific domestic coal (4087 kcal/kg) and high-calorific imported coal (5954 kcal/kg) were combusted at the single mill and burner level to analyze unit parameters at different loads. Initially, input parameters, levels affecting unit parameters, and output parameters influenced by different coal types were identified and prioritized. Using criteria weights determined by the entropy method, the optimal load and domestic-imported coal blend ratio were determined using the Preference Ranking Organization Method for Enrichment Evaluation-Geometrical Analysis for Interactive Aid (PROMETHEE-GAIA) multicriteria decision-making method. The optimization study concluded that a 450 MW load with a 14.6% domestic coal feed rate is the most suitable alternative.